Politik Emas Hijau: Aktor, Agensi, Dan Perdagangan Tembakau Di Madura - Abdullah Alwazin (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The term "golden leaves" or "green gold," often attributed to tobacco in Madura, symbolizes the significance of this commodity to the local population. As such, the selling price of tobacco plays a crucial role in shaping the economy of tobacco farming communities on the island. Between 2020 and 2023, a notable phenomenon occurred: the selling price of tobacco for farmers in Pamekasan and Sumenep increased. This rise is attributed to rural cigarette entrepreneurs who purchased tobacco from farmers at higher prices compared to previous years. Through an actor-oriented perspective study, I aim to show how selling prices fluctuate significantly in the tobacco trading ecosystem. The results of my study demonstrate how the agency of various actors emerges within different social, political, and economic conjunctures, collectively orchestrating the increase in tobacco purchase prices from farmers.